Star wars. - 2lcgft1# Lucas, George, 1944-; 2lcgft1# Lucas, George, 1944-; McCallum, Rick, 195; McGregor, Ewan; Portman, Nata 1971-; Christensen, Hay 1981-
After three years of fighting in the Clone Wars, Anakin Skywalker succumbs to the Dark Side of the Force, completing his tragic transformation into Darth Vader, Lord of t